Pediatric Glomerular Diseases (Review of histopathological subtypes). - Azat, Nariman F.A.; hameed, Numan N.; Sahib, Onss A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Glomerular injury can be caused by immunologic, infectious, toxic, metabolic and heamodynamic factors. The glomerular response to injury determines the pathology, which can be observed in renal biopsy. The purpose of this study was to analyze different histopathological subtypes of primary and secondary glomerular diseases in children.Patients and methods: A retrospective study was done on 100 renal biopsy cases in children welfare teaching hospital between December 2003 and December 2007. Ultrasonically guidedbiopsies were taken and only light microscopy was used to examine the specimens.Results: The study group included 100 cases with renal diseases, 83 (83%) cases of which having primary glomerular disease, the remainder 17 (17%) cases represented secondary glomerular disease. The patients age ranged between (1month-15 years).The frequency of the different entities of primary glomerular disease was: focal segmental glomerulosclerosis (FSGS %) 27 (27%), Minimal change disease22 (22%), Mesangioproliferative glomerulonephritis21 (21%), Mesangiocapillary Glomerulonephritis7(7%) and congenital nephrotic syndrome 6 (6%).patients with secondary glomerular diseases: 14 (14%) patients had Systemic Lupus Erythromatosis(SLE), 2(2%) Henoch- Schonlein Purpura and 1(1%) Amyloidosis .Conclusion: The results of this study were comparable to other studies, with Focal segmental glomerulonephritis being the most common primary glomerular diseases and systemic lupuserythromatosis being the most common secondary glomerular diseases in children. Further study on a much larger scale with the utilization of immunoflourescent and electron microscopy with full serology and infectious screening is needed to provide deeper understanding of these different diseases.